A content validity study of the test of valuers' support for capturing sustainability in the valuation process in Nigeria. (2nd September 2019) - Ibiyemi, Abayomi; Mohd Adnan, Yasmin; Daud, Md Nasir; Olanrele, Segun; Jogunola, Abiodun
ABSTRACT: Property valuers' support for sustainability has a significant impact on the resolution to reflect its dimensions in the valuation process. The study presents the content domain of the valuers' perception of sustainability reporting in Nigeria for the purpose of identification and eliciting the character. Based on informed judgment, it engages a panel of 5 experts who possess expertise in real estate valuation, environmental management and academics/consultancy to rate 26 items with a 4-point Likert scale for the content validity index (i-CVI), the scale content validity index (s-CVI) and the content validity ratio (CVR) grounded on relevance to the property valuers' willingness to capture sustainability in the valuation process.The results show that (i-CVI > 0.75 and; s-CVI>0.80. Lawshe's content validity ratio is at +0.692. The measuring scale is content-valid and the panel size is adequate at a Mean Proportion Agreeing of 0.876. Only 21 items should be adopted for a further Cronbach alpha test of reliability.The paper argued for consistent and explicit content validation in sustainability research to avoid probable chance effects. Content validation helps to provide reliable data for causal model development of the knowledge management (KM) requirements for the integration of sustainability into real estate valuation.